Effect of high pH on growth of Synechocystis sp. PCC 6803 cultures and their contamination by golden algae (Poterioochromonas sp.) - Touloupakis, Eleftherios (2016)
Culturing cyanobacteria in a highly alkaline environment is a possible strategy for controlling contamination by other organisms. Synechocystis PCC 6803 cells were grown in continuous cultures to assess their growth performance at different pH values. Light conversion efficiency linearly decreased with the increase in pH and ranged between 12.5 % (PAR) at pH 7.5 (optimal) and decreased to 8.9 % at pH 11.0. Photosynthetic activity, assessed by measuring both chlorophyll fluorescence and photosynthesis rate, was not much affected going from pH 7.5 to 11.0, while productivity, growth yield, and biomass yield on light energy declined by 32, 28, and 26 % respectively at pH 11.0. Biochemical composition of the biomass did not change much within pH 7 and 10, while when grown at pH 11.0, carbohydrate content increased by 33 % while lipid content decreased by about the same amount. Protein content remained almost constant (average 65.8 % of dry weight). Cultures maintained at pH above 11.0 could grow free of contaminants (protozoa and other competing microalgae belonging to the species of Poterioochromonas).